Feeding the world better: crop diversification to build sustainable food systems - Malézieux, Eric; Beillouin, Damien; Makowski, David (Perspective, 2022)
Version française de l'article Today, major changes are required in global agricultural systems to produce enough healthy food for all, while preserving the quality of land, air and water and safeguarding biodiversity. But producing enough while simultaneously protecting the environment is a particularly complex equation. Agroecology, a key principle of which is the use of agricultural biodiversity, is a promising pathway to achieve these changes. Extensive qualitative and quantitative evidence demonstrates the agricultural and environmental effectiveness of agroecological practices and confirms their capacity to meet the demands of global production in the long term. Among the possible diversification strategies, agroforestry, intercropping and crop rotation can all significantly increase production and enhance biodiversity and ecosystem services (soil quality, pest and disease control, water use and quality). This evidence can serve as a basis for new public policies to be introduced from the local to the global level. The implementation of such policies is crucial in climate-vulnerable regions where demand for food is growing, such sub-Saharan Africa.